Monitoring Trafik Jaringan Dan Pengaturan Pc Router Berbasis Web (Studi Kasus: Labkom Stikom Surabaya) - Oktario Wun, Yermias Alfandy; Sukmaaji, Anjik; Jatmika, Kurniawan (Jurnal JSIKA, 2014)
Abstract: admin constrained to manage a network traffic and limit bandwith usage and also block websites that are not allowed. Now, admin still used plug/unpulug way to manage the network on LABKOM STIKOM Surabaya. Based on problem occurred then needed an application which can provide information about activities that occurred on the local network to maintain network performance in LABKOM and also provide visual information about network traffic conditions in LABKOM and can facilitate a network administrator to restrict the use of bandwidth as well as the blocking of websites is not allowed during practical work takes place With SNMP, Data from the current network conditions can be collected and visualize the network traffic. And also requires an IPTables application to manage input and outputÂ the gateway. Expected by the existence of Monitoring network traffic and system settings to the Routers Web-based PC can provide information and facilities needed by a system LABKOM administrator network that makes it easy to monitor and control the internet access on the network LABKOM and minimize in terms of financial expenditure is excessive as the replacement schedule for practical and cost of electricity due to the presence of interference on the network LABKOM at the time of the process of teaching.